2015
DOI: 10.9755/ejfa.v27i1.17870
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in understanding cadmium toxicity and tolerance in rice

Abstract: Heavy metal bioaccumulation in the soil, water and atmosphere may be seriously hazardous to both human and animals with the contamination of food supply chain. Cadmium is a toxic heavy metal with no defined biological function. It is provided to environment mostly through effluent from sewage sludge, mining, burning, industries and fertilization with phosphate. Cadmium uptake and accumulation in rice (Oryza sativa L.) results in negative effect on plant growth. It inhibits physiological activities, such as pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 82 publications
0
2
0
1
Order By: Relevance
“…Cd is not needed for plant growth and development but is more likely to accumulate in plants than other heavy metals [3]. Evidence suggests that a high concentration of Cd in soil affects the growth and development of plants through physiological and biochemical processes, including inhibition of plant enzyme and membrane activity [4], decreased cell division [5], reduced growth rate [6], damaged photosynthesis [7], inhibition of stomatal opening [8], and promotion of lipid peroxidation [9]. Cd bioaccumulates and in humans can cause diseases such as osteoporosis, anemia, hypertension, and kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…Cd is not needed for plant growth and development but is more likely to accumulate in plants than other heavy metals [3]. Evidence suggests that a high concentration of Cd in soil affects the growth and development of plants through physiological and biochemical processes, including inhibition of plant enzyme and membrane activity [4], decreased cell division [5], reduced growth rate [6], damaged photosynthesis [7], inhibition of stomatal opening [8], and promotion of lipid peroxidation [9]. Cd bioaccumulates and in humans can cause diseases such as osteoporosis, anemia, hypertension, and kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…Research data from the Country Resource Department of China in 2009 showed that more than 10% of plantation land had been contaminated by toxic metals. Crops harvested from the contaminated soil contain excess toxic metals which may subsequently enter the human body through food chain, resulting in serious human health concerns (JAISHANKAR et al, 2014.;FASAHAT, 2014.;REN et al, 2003). Cadmium (Cd) is one of the toxic metals which threatened both environment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…chồi cây có tương quan thuận với sinh khả dụng của kim loại nặng trong đất14,15 . Khi nồng độ Cd tăng cao trong cải thìa, Cd can thiệp vào các quá trình logic vật lý của chúng, ví dụ như quang hợp và hô hấp, dẫn đến cải thìa chậm phát triển, đặc biệt là đất có nồng độ Cd vượt tiêu chuẩn (3 mg/kg và 6 mg/kg)16,17 . Khối lượng khô của thân và rễ cây cải thìa giảm 11,1% và 16,7% ở nồng độ Cd cao (6 mg/kg), so với nghiệm thức đối chứng (Bảng 2).…”
unclassified